Evaluating the Impact of Mothers' Self-esteem on Early Childhood Home Environment: Evidence from NLSY - Tirthatanmoy Das; Kabir Dasgupta (Auckland University of Technology (AUT), Faculty of Business, Economics and Law, 2018)
Estimating causal effects of parental characteristics on determinants of child outcomes is complicated due to endogeneity problems. Utilizing matched mother-child data from National Longitudinal Surveys of Youth, this paper integrates an orthogonalization technique to 2SLS-IV regressions. The key findings indicate that a rise in mothers' selfesteem improves children's home environment conditions that promote cognitive and emotional developments, with larger effects observed among mothers in socio-economically disadvantaged families. The magnitude of these effects are either higher than or comparable to the effects of mothers' education and cognitive ability. Additionally, we find that a rise in mothers' self-esteem improves children's reading abilities.
Keywords: C26; J13; J24; 330; Childhood Development; Home environment; Mothers' self-esteem; Instrumental variables; Orthogonalization